Health Information Technology- An Updated Review Data - Mana R, Alanazi Mushawah; Khamis Abdulrahman Jumah Alkhaibiry; Raed Abdullah Abdu Barakat; Mohammad Hamad Alawad; Saad Hazzaa Gazi Aljsh; Amsha Sameer Mulayhan; Hana Mureia Alameer; Ali Abdullah Ali Kariri; Ali Mohmmed Hig Sharahili; Qassim Arar Ahmed Alhaqawi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Health Information Technology (HIT) encompasses the hardware, software, and systems used to manage health information across the care continuum. It is fundamental to modern healthcare, aiming to improve accountability, patient outcomes, delivery efficiency, and cost containment. However, its widespread adoption presents significant challenges and unintended consequences that must be addressed. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This updated review provides a comprehensive analysis of the multifaceted impact of HIT, examining its potential benefits, critical issues of concern, and overall clinical significance within contemporary healthcare systems. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review synthesizes current literature and evidence on HIT’s core functions. It analyzes key areas including patient safety tools (e.g., CPOE), population health management, healthcare delivery efficiency, cost implications, and the significant barriers and risks associated with implementation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> HIT demonstrably improves patient safety through decision support (e.g., reducing medication errors) and enhances population health via surveillance and data analytics, as exemplified by its role in the Flint water crisis. It increases healthcare delivery efficiency by improving data access and, through evolving interoperability standards like FHIR, promises better care coordination. While HIT offers potential for long-term cost savings, initial implementation is prohibitively expensive for many institutions. Major concerns include "technologic iatrogenesis" such as cybersecurity threats (e.g., ransomware), alert fatigue, workflow disruptions, and the risk of exacerbating health disparities through a digital divide. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> HIT is an indispensable but double-edged sword in healthcare. Its benefits in safety, quality, and efficiency are substantial, yet they are counterbalanced by high costs, security vulnerabilities, usability problems, and equity challenges. Realizing HIT’s full potential requires continued investment in interoperability, robust cybersecurity, user-centered design, and policies that ensure equitable access.